Women's rights agenda and fragmented advocacy for safe abortion in Kenya. Issue 4 (19th May 2022) - Saharan, Tara; Schulpen, Lau
ABSTRACT: Restrictive abortion laws resulting in unsafe abortions form one of the key causes of maternal morbidity and mortality in Kenya. Despite the existence of several Women's Rights Organisations (WROs), advocacy for safe abortions against restrictive laws does not have the momentum the subject deserves. This research draws on agenda-setting literature to explore factors that impede advocacy initiatives of WROs against restrictive abortion laws in Kenya. Using qualitative methods, the article shows that women's rights agenda results from existing societal norms, funding priorities, state legislation, and lack of solidarity among WROs.